Recommendations on RBC Transfusions for Critically Ill Children With Nonhemorrhagic Shock From the Pediatric Critical Care Transfusion and Anemia Expertise Initiative. (September 2018) - Muszynski, Jennifer A.; Guzzetta, Nina A.; Hall, Mark W.; Macrae, Duncan; Valentine, Stacey L.; Bateman, Scot T.; Spinella, Philip C.
Abstract : Objectives: To present the recommendations and supporting literature for RBC transfusions in critically ill children with nonhemorrhagic shock developed by the Pediatric Critical Care Transfusion and Anemia Expertise Initiative. Design: Consensus conference series of international, multidisciplinary experts in RBC transfusion management of critically ill children. Methods: The panel of 38 experts developed evidence-based, and when evidence was lacking, expert-based clinical recommendations as well as research priorities for RBC transfusions in critically ill children. The nonhemorrhagic shock subgroup included five experts. Electronic searches were conducted using PubMed, EMBASE, and Cochrane Library databases from 1980 to May 2017. Agreement was obtained using the Research and Development/UCLA Appropriateness Method. Results were summarized using the Grading of Recommendations Assessment, Development, and Evaluation method. Results: Transfusion and Anemia Expertise Initiative Consensus Conference experts developed and voted on a total of four clinical and four research recommendations focused on RBC transfusion in the critically ill child with nonhemorrhagic shock. All recommendations reached agreement (> 80%). Of the four clinical recommendations, three were based on consensus panel expertise, whereas one was based on weak pediatric evidence. In hemodynamically stabilized critically ill children with a diagnosis of severe sepsis or septic shock, we recommend not administering a RBC transfusion if the hemoglobin concentration is greater than or equal to 7 g/dL. Future studies are needed to determine optimum transfusion thresholds for critically ill children with nonhemorrhagic shock undergoing acute resuscitation. Conclusions: The Transfusion and Anemia Expertise Initiative Consensus Conference developed pediatric-specific clinical and research recommendations regarding RBC transfusion in the critically ill child with nonhemorrhagic shock. Although agreement among experts was strong, available pediatric evidence was scant—revealing significant gaps in the existing literature.